A bacteriocin-based coating strategy to prevent vancomycin-resistant Enterococcus faecium biofilm formation on materials of interest for indwelling medical devices - Christian Kranjec; Jills Puthiaparambil Mathew; Kirill Ovchinnikov; Idowu Fadayomi; Ying Yang; Morten Kjos; Wen-Wu Li (Biofilm)
The ever-increasing use of exogenous materials as indwelling medical devices in modern medicine offers to pathogens new ways to gain access to human body and begin, in some cases, life threatening infections. Biofouling of such materials with bacteria or fungi is a major concern during surgeries, since this is often associated with biofilm formation and difficult to treat, recalcitrant infections. Intense research efforts have therefore developed several strategies to shield the medical devices' surface from colonization by pathogenic microorganisms. Here, we used dopamine as a coupling agent to coat four different materials of medical interest (plastic polyetheretherketone (PEEK), stainless steel, titanium and silicone catheter) with the bacteriocins, enterocin EJ97-short and the thiopeptide micrococcin P1. Water contact angle measurements and x-ray photoelectron spectroscopy were used to verify the effective coating of the materials. The effect of bacteriocins coated on these materials on the biofilm formation by a vancomycin resistant Enterococcus faecium (VRE) strain was studied by biofilm-oriented antimicrobial test (BOAT) and electron scanning microscopy. The in vitro biocompatibility of bacteriocin-modified biomaterials was tested on cultured human cells. The results demonstrated that the binding of the bacteriocins to the implant surfaces is achieved, and the two bacteriocins in combination could inhibit biofilm formation by E. faecium on all four materials. The modified implant showed no cytotoxicity to the human cells tested. Therefore, surface modification with the two bacteriocins may offer a novel and effective way to prevent biofilm formation on a wide range of implant materials.